Development of Physics E-modules Based on Problem Based Learning Model Assisted by Heyzine Flipbook to Improve Problem Solving Ability - Sinaga, Natalia; Hanisa Putri, Desy; Medriati, Rosane (UNIVERSITAS INDRAPRASTA PGRI, 2025)
This study aims to validate the feasibility of physics e-modules based on Problem Based Learning (PBL) model assisted by heyzine flipbook, improve students' problem solving skills after using physics e-modules based on PBL model assisted by heyzine flipbook, and describe students' responses to physics e-modules based on PBL model assisted by heyzine flipbook. The research was conducted in class XI of SMA Negeri 6 Bengkulu City in the 2024/2025 academic year. With the R&D method and ADDIE model. The results of the research from the product validation test stage with a score of 86% (very feasible category) to be used in the physics learning process. The results of the N-gain value through the prettest and posttest tests obtained a score of 0.75 (high category) so that the physics e-module can improve students' problem solving skills. The results of the student response questionnaire obtained a score of 81% (very good category). It can be concluded that the physics e-module based on the PBL model assisted by heyzine flipbook gets a positive response from students.